ACTIVE LOWER RANGE OF MOTION BERBANTU KAYU REFLEKSI MENINGKATKAN KELEMBABAN KAKI PASIEN DIABETES MELITUS TIPE II - Rahayuni, Ni Made Ayu; Sukarja, I Made; Surasta, I Wayan (Coping: Community of Publishing in Nursing; Vol 10 No 1 (2022): Februari 2022DO - 10.24843/coping.2022.v10.i01.p03, 2022)
Sudomotor autonomic neuropathy decrease the function of the sweat glands (eccrine) so that the skin of the foot becomes dry and cracked may predispose the diabetic foot. This study aimed to determine the effect of active lower range of motion assisted by wooden reflexology roller on the foot moisture of diabetic patient. In this quasi-experimental research with pre and post-test design with the control group, 36 diabetic patients with T2DM ?3 years, aged ?50 years, and did not have diabetic or gangrenous ulcers were grouped into the treatment group, which was given an active lower range of motion assisted by wooden reflexology roller, and the control group, which was given standard treatment. The average humidity of the treatment group increased from 24.75% to 43.48% with the p-value 0,000 (? = 0,05). While the control group’s feet moisture increased from 27.1% to 32.4% with a p-value 0.000. The p-value of independent sample t-test between treatment group and control resulted 0,000 (? = 0,05). According to the results, it can be concluded that there was a significant influence between active role ROM assisted wood reflection and the moisture of DM type II patient's feet.